(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2011)
Geological-geographical peculiarities of the district of Halidzor–Tatev ropeway construction has been described. The appraisal of geomorphological and engineering-geological conditions for determination of stability of areas for construction of stations (terminals) and piers of the ropeway is given.